Prevalence of Candida species and their antifungal susceptibility patterns among patients in tertiary care setting Butwal, Nepal: A cross-sectional study - Sachin BK; Roka, Bhumi; Bishwokarma, Barsha; Yadav, Baliram; Chaudhary, Gautam Prasad; Pandey, Jitendra; Karki, Khimdhoj; Khadka, Ram Bahadur (Asian Journal of Medical Sciences, 2024)
Background: Candida species, commonly present in the human body, can result in severe infections. Non-albicans Candida (NAC) species, with increasing antifungal resistance, pose a growing concern. Aims and Objectives: This study aims to evaluate candidiasis prevalence and antifungal susceptibility in isolated Candida species among suspected patients at tertiary care hospitals in Butwal, emphasizing early identification and appropriate treatment to avoid unnecessary use of toxic antifungal drugs. Materials and Methods: In a descriptive study on 303 patients with clinical symptoms of Candida infections, specimens underwent direct microscopic examination and culture on Sabouraud dextrose agar. Species identification involved phenotypic methods such as chromogenic character on CHROMagar Candida media, germ tube examination, and microscopic characteristics. Subsequently, isolated species were tested for antifungal susceptibility using the disc diffusion method. Results: Among the 303 samples tested, 80 (26.4%) were positive for candidal infection. NAC species were the most commonly isolated, with Candida albicans and Candida krusei being the most virulent. The isolates exhibited the highest sensitivity to fluconazole (77.5%) followed by itraconazole (75%), whereas amphotericin B showed the lowest effectiveness with 63.75% resistance. Conclusion: The rising prevalence of NAC species, particularly their growing resistance to Amphotericin B, has become a significant concern, as these species are frequently detected in various clinical samples. These findings underscore the importance of diligent monitoring and judicious selection of antifungal agents to ensure effective treatment strategies.